2019
DOI: 10.1177/1470595819887192
|View full text |Cite
|
Sign up to set email alerts
|

The importance of team psychological safety climate for enhancing younger team members’ innovation-related behaviors in South Korea

Abstract: Indigenous cultural nuances such as age-related hierarchies in South Korea have the potential to impact workers’ engagement in innovation-related behaviors (IRBs). We use self-categorization theory to examine both the relationship between employee age and IRBs and the cross-level interaction effects of team psychological safety climate. Using a multilevel sample of 282 South Korean employees working in 65 teams across 45 different organizations in various industries, we find that team psychological safety clim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 66 publications
0
2
0
1
Order By: Relevance
“…In other words, team members are less concerned about interpersonal risks, including negative impressions of themselves, arising from workplace anxiety caused by self-serving leadership. Thus, high levels of team psychological safety can effectively relieve employees' fear of a negative impact (Moake et al, 2019 ); self-control of resource consumption provides relief. In addition, as an organizational support resource, team psychological safety can help replenish the resource depletion caused by the anxiety of team members (Grandey et al, 2012 ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…In other words, team members are less concerned about interpersonal risks, including negative impressions of themselves, arising from workplace anxiety caused by self-serving leadership. Thus, high levels of team psychological safety can effectively relieve employees' fear of a negative impact (Moake et al, 2019 ); self-control of resource consumption provides relief. In addition, as an organizational support resource, team psychological safety can help replenish the resource depletion caused by the anxiety of team members (Grandey et al, 2012 ).…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Par exemple, Moake et al (2019) ont révélé que la sécurité psychologique protège contre les effets potentiellement négatifs de la diversité liée à l'âge. En outre, les personnes appartenant à des groupes minoritaires perçoivent généralement une sécurité psychologique inférieure à celle des employés caucasiens (Derickson et al, 2015).…”
Section: Différences Individuellesunclassified
“…IWB, thus, is fostered in an environment that provides a risk-free atmosphere to employees (Kanfer & Ackerman, 1989). Previous research has considered a climate that fosters psychological safety among employees as a critical element for enhancing innovative employee behaviors in organizations (Baer & Frese, 2003;Moake et al, 2019;Mansur et al, 2017). Other research has found positive effects on the psychological safety climate for employee IWB (Moake et al, 2019) Hypotheses 5 to 7 concerned the mediation of psychological safety between the dimension of PL and IWB.…”
Section: Figure 3 Structural Modelmentioning
confidence: 99%